2014
DOI: 10.1242/dev.105932
|View full text |Cite
|
Sign up to set email alerts
|

Prickle/spiny-legs isoforms control the polarity of the apical microtubule network in planar cell polarity

Abstract: Microtubules (MTs) are substrates upon which plus-and minus-end directed motors control the directional movement of cargos that are essential for generating cell polarity. Although centrosomal MTs are organized with plus-ends away from the MT organizing center, the regulation of non-centrosomal MT polarity is poorly understood. Increasing evidence supports the model that directional information for planar polarization is derived from the alignment of a parallel apical network of MTs and the directional MT-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
149
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(160 citation statements)
references
References 42 publications
7
149
3
1
Order By: Relevance
“…As it turns out, these polarized microtubule arrays can bias the transport of core PCP particles consisting of Dsh, Fz and Fmi towards one side of the cell, aiding the PCP patterning process 3639 . These Fmi–Fz–Dsh accumulations are preferentially trafficked towards the plus ends of microtubules, showing a bias in directionality similar to plus-end tip tracking proteins such as EB1 38 (Fig. 2).…”
Section: Establishment Of Core Pcp Patternsmentioning
confidence: 94%
See 3 more Smart Citations
“…As it turns out, these polarized microtubule arrays can bias the transport of core PCP particles consisting of Dsh, Fz and Fmi towards one side of the cell, aiding the PCP patterning process 3639 . These Fmi–Fz–Dsh accumulations are preferentially trafficked towards the plus ends of microtubules, showing a bias in directionality similar to plus-end tip tracking proteins such as EB1 38 (Fig. 2).…”
Section: Establishment Of Core Pcp Patternsmentioning
confidence: 94%
“…It has separately been shown that intact PCP patterns are necessary for the polarization of microtubule arrays 24,38,41 , demonstrating that intricate and mutual relationships exist between microtubule polarity and planar polarity patterning.…”
Section: Establishment Of Core Pcp Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Ds–Ft activity orients microtubules and thus participates in Fz and Dsh trafficking to the distal side of a cell to reinforce initial polarity [17,18]. Also, Pk isoforms have recently been shown to couple Ds–Ft to the core system at late stages of PCP reinforcement by ‘interpreting’ the Ds–Ft gradient to orient microtubules [19,20]. The new work from Hale et al .…”
mentioning
confidence: 99%